Pengaruh Kualitas Produk dan Sosial Media Marketing terhadap Keputusan Pembelian Melalui Kepercayaan Merek pada J.Co Donut’s & Coffee di Jabodetabek - Sintia Ratnaningsih; Ra Nurlinda (Journal Economic Excellence Ibnu Sina, 2024)
This research aims to determine the direct and indirect influence between product quality, social media marketing, brand trust on purchasing decisions among J.Co Donut's & Coffee consumers in Indonesia. The method used is Path analysis using a Structural Equation Modeling (SEM) approach with data collection using a questionnaire distributed online to 190 respondents who are active social media users and customers of J.Co Donut's & Coffee. The results of the analysis show that product quality and social media marketing have a direct positive influence on brand trust and purchasing decisions, while brand trust does not have a direct influence on purchasing decisions. Brand trust is not proven to be a mediating variable between product quality and social media marketing on purchasing decisions. These findings provide important insights for companies in developing marketing strategies and understanding the factors that influence consumer purchasing behavior, emphasizing the importance of product quality and marketing strategies via social media in building brand trust and influencing purchasing decisions.